Robot Controlled by Voice Using Mobile Phone - Ashish, Abhijeet; Gautam, Gaurav; Kumar, Anil (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
This paper includes that how a robot works with the input given in voice. this paper explains that how a robot interface with user with voice command given by the user. This system is quite fast. this system consists three parts first one is voice recognition system second one is central controller system and third one is robot. The voice recognition system is a basically a interface between man and robot it receives the voice as input signal and processes it and then forwarded to central controller then it passes the signal to Robot. The paper will describe how the whole process it happen. In this system the human work will become quite easy to give commanding signal because there is no use of hands or any other part come into existence. In this system the robot will be quite familiar with humans.